A traveling salesman problem with time windows for the last mile delivery in online shopping. Issue 16 (17th August 2020) - Jiang, Li; Dhiaf, Mohamed; Dong, Junfeng; Liang, Changyong; Zhao, Shuping
Abstract : With the fast growth of the parcel volume of online shopping, home delivery (delivering parcels to customers' homes or workplaces) has accentuated the pressure on last mile delivery actors. Customer pickup, which allows customers to pick up their parcels from shared delivery facilities near them, has become widely popular. This study introduces a novel travelling salesman problem with time windows for the last mile delivery in online shopping. The purpose is to find a minimum cost tour over given customers and/or shared delivery facilities (SDFs) in which unvisited customers are assigned to the SDFs. A general variable neighbourhood search heuristic is developed to solve the problem. Computational results corroborate that the proposed heuristic is competitive relative to well-known algorithms.